Multimedia vositalari asosida talabalarni madaniyatlararo kommunikativ kompetensiyalarini rivojlantirish texnologiyalari - Tleumuratova, A.B (SCIENCE and SOCIETY, 2023)
This article describes the technologies for the development of intercultural communicative competence of
Keywords: technologies; innovative education; intercultural communicative competence; competence